Effect of Cooperative Learning Model Numbered Head Together (NHT) to Social Attitudes Toward Competency Seventh Grade Students of SMPN 1 Padang - Toeenfi Febrian Suzerli; Heffi Alberida; Relsas Yogica (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
Learning science in SMPN 1 Padang has been running pretty well in accordance with the curriculum of 2013. However, there are still shortcomings in the aspect of attitude. Such as low self-care among others, mutual esteem is very low when friends come forward, attitudes tend to be selfish and apathetic attitude towards the environment, resulting in low competence of the social attitudes of learners. One of the ways that teachers can do is to implement cooperative learning model Numbered Head Together (NHT). This study aims to determine the effect of cooperative learning model Numbered Head Together (NHT) the competence of the social attitudes of students of class VII SMPN 1 Padang. This study was an experimental study with a quasi-experimental methods (quasi-experimental). The study population was the students of class VII SMPN 1 Padang. Sampling was done by purposive sampling with learners VII.D class as the control class and the class as a class experiment VII.E. The instrument used is the observation sheet attitude competence of learners. The result shows that there are improvement of students social attitude competence after using NHT in class VII SMPN 1 Padang. Factors include are discussed.